The Place and Role of Fundamental Rights in the EU Legal System - Masło , Krzysztof (The Policies of the European Union from a Central European Perspective, 2022)
The protection of fundamental rights at European level has been one of the most important issues since the founding of the Communities. An important gap was filled by the Lisbon Treaty when it incorporatedthe Charter of Fundamental Rights into primary EU law. Its scope, interpretation, and relationship with national constitutions and legal systems has been the most controversial issue of the last decade. After apresentation of the historical development of the protection of fundamental rights in Europe, this chapterlooks at the issues of application of the Charter of Fundamental Rights in the jurisprudence of the EasternEuropean countries. Keywords: Charter of Fundamental Rights, direct application of EU law, judicial cooperation in criminal matters, principle of mutual trust, protection of fundamental rights